Essential Atlas of Biology (New delhi Sterling, 2006)
This information- packed atlas combines text,photos, and illustrations to tell the storyof the life in its many forms- plants, animals, and even amoeba,bacteria, and fungi
Consistes of index
11 12
Keywords: Science(animals); Science(plants)